15. Rethinking the Mesolithic of the Sado Paleoestuary, Portugal: Semi-sedentary Hunter-gatherers - Soares, Joaquina (2019)
The Mesolithic economy of the Sado palaeo-estuary developed parallel to the early stage of food production economy (5700–5300 cal. BC) of the Southwest Portuguese Coast. The Sado Mesolithic communities adopted pottery probably from them, as it was useful for storage but they did not take up their agricultural economy for more than a millennium, maintaining a demographicecological balance until 4500/4000 cal. BC. The author presents a synthesis about the Mesolithic of the Sado palaeo-estuary, building a theoretical model of socio-economic dynamics in a longterm perspective.